The ATP-dependent chromatin remodeler Chd1 is recruited by transcription elongation factors and maintains H3K4me3/H3K36me3 domains at actively transcribed and spliced genes - Lee, Yaelim; Park, Daechan; Iyer, Vishwanath R. (OXFORD UNIV PRESS, 2017)
Chd1 (Chromodomain Helicase DNA Binding Protein 1) is a conserved ATP-dependent chromatin remodeler that maintains the nucleosomal structure of chromatin, but the determinants of its specificity and its impact on gene expression are not well defined. To identify the determinants of Chd1 binding specificity in the yeast genome, we investigated Chd1 occupancy in mutants of several candidate factors. We found that several components of the PAF1 transcription elongation complex contribute to Chd1 recruitment to highly transcribed genes and identified Spt4 as a factor that appears to negatively modulate Chd1 binding to chromatin. We discovered that CHD1 loss alters H3K4me3 and H3K36me3 patterns throughout the yeast genome. Interestingly, the aberrant histone H3 methylation patterns were predominantly observed within 1 kb from the transcription start site, where both histone H3 methylation marks co-occur. A reciprocal change between the two marks was obvious in the absence of Chd1, suggesting a role for CHD1 in establishing or maintaining the boundaries of these largely mutually exclusive histone marks. Strikingly, intron-containing genes were most susceptible to CHD1 loss and exhibited a high degree of histone H3 methylation changes. Intron retention was significantly lower in the absence of CHD1, suggesting that CHD1 function as a chromatin remodeler could indirectly affect RNA splicing.
Keywords: RNA-POLYMERASE-II; SACCHAROMYCES-CEREVISIAE; PROSTATE-CANCER; HISTONE H3K4; BIOCONDUCTOR PACKAGE; METHYLATION; YEAST; EXPRESSION; GENOME; SEQ